Cross - Cultural Communication Strategies Used By Hostess At Holiday Inn Express Baruna Bali During Breakfast Service - Padma Narayani, Ni Kadek Diah; Susena Suyasa, Made Dharma; Marsakawati, Ni Putu Era (Innovative: Journal Of Social Science Research, 2025)
This study explores the cross-cultural communication strategies employed by hostess at Holiday Inn Express Baruna Bali when serving guests during breakfast. This study aims to analyze the cross-cultural communication strategies employed by hostess at Holiday Inn Express Baruna Bali when interacting with guests from several cultural backgrounds.. Using a qualitative approach, data were collected through distributed an online questionnaire. Participants of this study were hostesses at Holiday Inn Express Baruna Bali who has responsibility to do courtesy during breakfast services. The method of collecting data were carried out in stages, from preparing questionnaire to obtaining data to create a report. The data analysis carried out by conducting close reading, identifying themes, and descriptive narrative preparation because the data produced was in the form of short answers from correspondents. The results of this study showed that hostess implemented various techniques, such as the use of simple and clear language, and recognition of guests' cultural habits and preferences. In addition, adaptations in communication styles, such as the use of non-verbal cues and empathy, were proven effective in building good relationships. This study highlights the importance of cross-cultural communication training for hotel hostess to enhance guest experiences and create a welcoming environment. These findings are expected to be a reference for hotel managers in designing better training programs and improving service quality in the hotel industry.